A Fictional Actuality - Creutzburg, Lennart (Taideyliopiston Kuvataideakatemia, 2023)
A Fictional Actuality explores the field of hybrids and the role of science fiction in society and in contemporary art. The human, considered as a machine driven by desire, is proposed to be affected and manipulated by hazardous environments like capitalists society's and surveillance capitalists. The entirety of the Master thesis is linked with the artistic component mixed-media installation 'as rhizomes whisper' by Lennart Creutzburg.
Keywords: as rhizomes whisper; kuvataide; nykytaide; installaatiot; veistokset; tilataide; taiteellinen työ; psychoanalytic theories; philosophy; science fiction (literature); capitalism; data; machine industry; human being; fi=kuvanveisto|sv=skulptur|en=Sculpture|